INOVASI TEKNOLOGI URBAN FARMING: ANALISIS LITERATUR TENTANG EFEKTIVITAS HIDROPONIK, VERTIKULTUR, DAN AKUAPONIK DI PERKOTAAN - Rita Hayati; Al-Amin (Adisam Publisher, 2025)
Urban farming is an agricultural innovation that is rapidly developing in urban areas in response to land constraints and increasing food demand. This study aims to analyse the effectiveness of three main urban farming technologies, namely hydroponics, vertical farming, and aquaponics, through a literature review. The analysis results indicate that hydroponics offers optimal water use efficiency and nutrient control, resulting in high-quality yields on limited land. Vertical farming maximises the use of vertical space, increases productivity, and provides aesthetic value to the urban environment. Meanwhile, aquaponics integrates fish farming and plant cultivation in a closed system, producing two commodities simultaneously while conserving water and land resources. Although these three technologies have significant advantages, challenges such as initial investment requirements, dependence on electricity and clean water, and the need for technical knowledge remain major obstacles. Policy support, training, and cross-sector collaboration are essential to expand the adoption and sustainability of urban farming technologies in urban areas. Overall, innovations in hydroponic, vertical farming, and aquaponics technologies have the potential to become strategic solutions for achieving food, economic, and environmental sustainability in the future.